Epidemiology and etiology of blood stream infections in a Belgian burn wound center. Issue 2 (4th March 2022) - Costescu Strachinaru, Diana Isabela; Gallez, Jean-Luc; François, Pierre-Michel; Baekelandt, Dries; Paridaens, Marie-Sophie; Pirnay, Jean-Paul; De Vos, Daniel; Djebara, Sarah; Vanbrabant, Peter; Strachinaru, Mihai; Soentjens, Patrick
ABSTRACT: Background: Infections are a major cause of morbidity in burn patients. We aimed to investigate the epidemiology and antibiotic susceptibility of blood stream infections in order to gain a better understanding of their role and burden in our Burn Wound Center. Methods: This retrospective epidemiological investigation analyzed data derived from medical files of patients admitted to our Burn Wound Center having had at least one positive blood culture between 1 January and 31 December 2018. We focused on the prevalence of causative agents in blood stream infections in function of the time after injury and on their drug sensitivity. Results: Among the 363 patients admitted to our Burn Wound Center during the study period, 29 had at least one episode of blood stream infection. Gram-negative organisms accounted for 56, 36% of the pathogens in blood stream infections, Gram-positives for 38, 17%, and yeasts for 5, 45%. Pseudomonas aeruginosa was the most common bacterium (20%), followed by Staphylococcus epidermidis (16.36%), Escherichia coli and Klebsiella pneumoniae (9, 09% each). A third of the Gram-negative isolates were multidrug resistant. Gram-positive cocci were isolated from blood cultures at a median of 9 days after the injury, earlier than Gram-negative rods (median 15 days). The main sources of blood stream infections were the burn wounds, followed by infected catheters. Conclusions: Multidrug resistant bacteria must be considered when selecting empirical antibiotic therapy in septic burn patients. In our center, we need to update our antibiotic guidelines, to review the hospital infection control measures and to introduce routine typing technology.